2013
DOI: 10.2147/rip.s32811
|View full text |Cite
|
Sign up to set email alerts
|

Designing strategies for the control of coccidiosis in chickens on poultry farms using modern diagnostic tools

Abstract: Abstract:Coccidiosis is caused by the intracellular protozoan parasite Eimeria and is a major worldwide problem in the poultry industry today. The current strategies to control the disease still rely heavily on anticoccidial drugs and on the use of shuttle programs to periodically introduce attenuated live parasites onto poultry farms. Recently, because of the improved performance of broiler chickens, farmers are able to raise chickens for market within a period of only 5-6 weeks. This short growth period enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Use of PCR has been hampered by characteristics of eimerian biology such as the oocyst wall's resilience to all but mechanical destruction, access to template DNA being restricted, and PCR being inhibited by the surrounding feces. Very few research has focused on the usability of these approaches for identifying Eimeria spp., despite the fact that various PCR tests have been developed to identify particular Eimeria species [13,24,25]. Using Eimeria oocysts enriched by flotation in saturated sugar and performing a freeze thaw 5 times to break up the oocyst walls greatly increased the sensitivity of the PCR [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of PCR has been hampered by characteristics of eimerian biology such as the oocyst wall's resilience to all but mechanical destruction, access to template DNA being restricted, and PCR being inhibited by the surrounding feces. Very few research has focused on the usability of these approaches for identifying Eimeria spp., despite the fact that various PCR tests have been developed to identify particular Eimeria species [13,24,25]. Using Eimeria oocysts enriched by flotation in saturated sugar and performing a freeze thaw 5 times to break up the oocyst walls greatly increased the sensitivity of the PCR [3].…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that 20 oocysts of each species were insufficient for PCR-based species identification [3]. Although the test worked well with pure genomic DNA, it decreased a part of its sensitivity and variety of identification of species when used with the typical field samples [25]. Early identification of bovine Eimeria species is importance for effective control of clinical and subclinical eimeriosis.…”
Section: Discussionmentioning
confidence: 99%